2019
DOI: 10.1029/2018jd029625
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Drying of Northeast India in the Last Three Decades: Climate Change or Natural Variability?

Abstract: Northeast India (NEI), the wettest place on the Earth, has experienced a rapid decrease in summer monsoon rainfall (about 355 mm) in the last 36 years (1979–2014), which has serious implications on the ecosystem and the livelihood of the people of this region. However, it is not clear whether the observed drying is due to anthropogenic activities or it is linked with the global natural variability. A diagnostic model is employed to estimate the amount of recycled rainfall, which suggests that about 7% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 48 publications
(62 reference statements)
2
38
0
Order By: Relevance
“…The diurnal variation of rainfall is from TRMM‐3B42 hourly precipitation data, which have a spatial resolution of 0.25° × 0.25°. We use TRMM‐3B42 data instead of ground‐based rain‐gauge stations because of the fewer number of rain‐gauge stations in the hilly terrain of NEI (Choudhury et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The diurnal variation of rainfall is from TRMM‐3B42 hourly precipitation data, which have a spatial resolution of 0.25° × 0.25°. We use TRMM‐3B42 data instead of ground‐based rain‐gauge stations because of the fewer number of rain‐gauge stations in the hilly terrain of NEI (Choudhury et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Krishnamurthy and Krishnamurthy, ; Choudhury et al . ). The decadal variability affects the monsoon through tropical Pacific variability.…”
Section: Introductionmentioning
confidence: 97%
“…Chattopadhyay et al, 2015) as well as on decadal time-scales (e.g. Krishnamurthy and Krishnamurthy, 2014;Choudhury et al, 2018). The decadal variability affects the monsoon through tropical Pacific variability.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of climate change on precipitation has been studied largely on the regional scale than global scale [2,32,33]. Majority of these studies focused on finding the changes in climate extremes [25,[34][35][36]. Raghvendra et al [35] reported the increase in number and intensity of thunderstorm in the Congo Basin, Central Africa; however, the net rainfall was found to be decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas and Nigam [37] reported the expansion of Sahara desert, South Africa, and warming trends of Southern regions than Northern regions. Choudhary et al [36] detected a rapid decrease in monsoon rainfall in the wettest place on the earth, North-East India, in the last four decades. The changes in annual total precipitation directly affect the water budget of the regions and are crucial for maintaining adequate water resources.…”
Section: Introductionmentioning
confidence: 99%